عہد حاضر میں مساوی اورسستے انصاف کی عدم فراہمی اوراس کا حل سیرت النبی ﷺ کی روشنی میں: Non-provision of equal and cheap justice in the present era and its solution in the light of the Prophet's life - Syed Ashfaq Ahmad (International Research Journal of Arabic and Islamic Studies, 2025)
Today, there is an ideological conflict between the different social and economic systems of the world.No region of the world is safe from it today.The imperialist powers are making the world a hell by heating up the market of cruelty for their personal interests. They are killing justice for their oppressive rule and to control the resources of the world.They can attack any country they want with ammunition and heat up the market of murder and murder, there is no stopping them. International courts seem completely unable to give justice to the weak.Similarly, if we talk about equal and cheap justice to the people living in a state, then in most countries, the class system is an obstacle in the way of justice and Equality.Nowadays, equal and cheap justice has become a dream for a vulnerable person.In such circumstances, we can say with full confidence that all the countries of the world can get equal and cheap justice at the internal and international level only by following the life of Prophet Muhammad ﷺ. The social and economic system of Islam or the system of justice and equality of Islam is life-giving for the entire humanity.If we study the conditions before the arrival of the Prophetﷺ, then in the Arab society there was a market of oppression and oppression similar to the conditions we are facing today. Muhammadﷺ brought the honor and it became the cradle of Arab justice and equality.